Pengaruh Model Pembelajaran Discovery Learning terhadap Peningkatan Motivasi dan Hasil Belajar Siswa pada Materi Ikatan Kimia kelas X SMKN 1 Panggul - Siti Mudawamah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Learning model is a conceptual framework that describes the procedure for organizing learning experiences to achieve learning objectives. This research is a Discovery Learning model class action research that aims to describe the motivation and learning outcomes of class X students of SMKN 1 Panggul on Chemical Bonding materials. This research is carried out in two cycles with each cycle consisting of four stage : planning, implementation, observation and reflection. Based on the results of data analysis, there was an increase in learning outcomes by 12% in cicle I and 16% in cycle II as seen from the results of pretest and posttest. Student motivation in learning chemical bonds in cycle I by 64,50% and in cycle II by 79%. This suggests that the Discovery Learning model is suitable for use in the study. It can be concluded that there is an increase in motivation and learning outcomes of class X students of SMKN 1 Panggul on chemical bonding material using the application of Discovery Learning.